Bioaccumulation Pattern of Heavy Metals in the Shrimps of the lower stretch of the River Ganga - Mitra, A.; Banerjee, K.; Ghosh , R.; Ray, S.K. (Mesopotamian Journal of Marine Sciences, 2022)
Rapid industrialization and urbanization have contaminated the riverine and estuarine ecosystems to a great extent. To evaluate such kind of contamination, we undertook a research programme to analyze the concentrations of zinc, copper, lead and cadmium in muscle tissue of five commonly edible shrimp species, namely Penaeus monodon, Penaeus indicus, Penaeus semisulcatus, Penaeus marguensis and Metapenaeus brevicornis collected from the lower stretch of the River Ganga (in the Sundarbans delta complex). The heavy metals in tissue samples were estimated using a Perkin-Elmer Sciex ELAN 5000 ICP mass spectrometer. Concentrations in shrimp species ranged as follows: Zn: 4.11 ± 0.13 – 353.45 ± 2.98; Cu: 3.43 ± 0.10– 140.49 ± 1.81; Pb: BDL - 8.21 ± 0.63 and Cd: BDL – 3.66 ± 0.12 mg kg-1 dry weight. Irrespective of species, heavy metals accumulated in the shrimp muscle in the order Zn > Cu > Pb > Cd. The concentration of heavy metals in the tissues varied significantly depending upon the locations from where the species were collected. Although the concentration of selected heavy metals were within the normal range in all stations, but at station 1 (Nayachar Island) the metal level has exceeded in the muscle of shrimp species as a food source for human consumption. The shrimp samples were collected from different locations of lower Gangetic region with different degree of industrial and anthropogenic activities and station 1 is exposed to maximum stress (in terms of pollution) from the adjacent port-cum-industrial zone of Haldia and industrial discharge of multifarious industries situated in and around the city of Calcutta (upstream to station 1) along the bank of the River Ganga.